Hand Washing Compliance among Food Handlers in the School Food Service Operations - Nornazira Suhairom; Rosini Abu; Abdullah Mat Rashid (Jurnal Dinamika Pendidikan dan Pembelajaran, 2015)
This study utilized an extended Theory of Planned Behavior (TPB) with the addition of descriptive norms and barriers constructs. The variables studied were knowledge, attitude, subjective norms, descriptive norms, perceived behavioral control, barriers, intentions and behavior of hand washing. This study involved 146 food handlers who work in 18 hostels kitchen from two types of boarding schools in Peninsular Malaysia. It was found that overall, most of the respondents demonstrated high level of attitude, subjective norms, descriptive norms, perceived behavioral control, barriers, intention and behaviors of hand washing. Result shows an average of high means of all constructs of the extended TPB. Results from the self-reported hand washing among food handlers in the foodservice operations of boarding schools suggest that an improvement should be made to the hand washing practices among food handlers. Some respondents admitted to sometimes not carrying out hand washing behavior properly, signifying that hand washing compliance are disputed. These findings have important practices implications where all food handlers should adhere to the hand washing guidelines as proposed by the Ministry of Health and the Ministry of Education to make sure they produce safe and clean foods.